The use of intelligent remote monitoring system in ship energy efficiency management based on internet of things. (5th March 2022) - Deng, Jianhua; Mai, Songyan; Zeng, Ji; Zhang, He; Jin, Bowen; Bu, Longyu; Huang, Chaochun; Jiang, Hui
The purpose is to carry out remote monitoring of ships and realise intelligent recording of ship energy efficiency. Big data technology, 6G communication technology and embedded technology are used to build a remote monitoring system of ship operation energy efficiency from the level of hardware and software. The specific research work can be divided into three aspects. First, the existing ship operation energy efficiency indicators are analysed, and the ship Energy Efficiency Operation Indicator (EEOI) with the most balanced performance is found as the evaluation indicator of ship operation energy efficiency. Then, the requirement analysis is carried out, and the overall framework design is completed according to the analysed requirements. Moreover, the hardware module selection and peripheral circuit design are completed based on the framework parameters. Finally, the software part of the system is built. The test results prove that the functionality and stability of the platform meet the actual needs. Then, the system is tested on board for 20 days. The system proposed has a certain reference value to help ships in China achieve energy saving and emission reduction.